ACCOUNTING DALAM PENGGUNAAN DANA DESA DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL PEMODERASI - Aprisda Ridho Wicaksono; Rahmiati Rahmiati; M. Ichsan Diarsyad (Universitas Palangka Raya, 2023)
This study aims to test the influence of bystander effect on fraud accounting in the use of village funds with individual morality as moderating variables. This research is quantitative research with descriptive approach. The population in this study is all village offices in Pangkalan Lada District, West Kotawaringin Regency. Sampling Technique using purposive sampling method. The sample in this study was village officials who worked in Pangkalan Lada Sub-District Village Office provided that the respondents in question had at least worked for one year in the Village Office. The sample in this study amounted to 67 respondents. The method of collecting data is using questionnaires that are distributed directly. The data used in the study is primary data collected through questionnaire surveys. Data analysis uses multiple linear regression analysis and moderation regression analysis (MRA) with an analytical approach. The results of multiple linear analysis research showed that bystander effect positive and significant effect on fraud accounting. Moderation regression analysis shows that individual morality is not able to moderate the bystander effect on fraud accounting.